MACROECONOMIC STABILITY AND ECONOMIC GROWTH IN CENTRAL AND EASTERN EUROPEAN COUNTRIES: EVOLUTION AND NEW CHALLENGES - Yuriy Bilenko (Baltic Journal of Economic Studies)
The objective of this article is to analyse the processes of macroeconomic stabilisation in Central and Eastern European countries over the past thirty years (1991-2021), from the inception of market reforms to the present day. At the same time, the author aims to identify patterns and trends in the macroeconomic policies of these countries, which were formed under the influence of radical structural changes, economic cycles and the global financial crisis of 2008. Methodology. In order to analyse the data, the correlation between variables was measured. The volatility of macroeconomic indicators was gauged using the standard deviation. Based on panel regressions with fixed effects, models were created to demonstrate the influence of macroeconomic stability on economic growth in 15 countries across Central and Eastern Europe over a 30-year period (1991-2021). Results. The analysis using panel regressions with fixed effects shows a significant impact of macroeconomic stability indicators on economic growth after the 2008 global financial crisis, compared to a very small impact during the 2000-2008 boom. The growth of indicators of the real effective exchange rate and total official reserves have a positive impact on economic growth during the boom, while the impact of these indicators decreases significantly in the post-crisis period, and the impact of the lending rate, the current account balance and the unemployment rate increases. It should be noted that the dominant positive factor influencing economic growth in all periods is the budget balance and the weak influence of the exchange rate. Practical implications. The author identifies certain combinations of macroeconomic indicators to create a successful macroeconomic policy for sustainable economic growth in Central and Eastern Europe. Value / Оriginality. The paper assesses and analyses the relationship between macroeconomic stability and economic growth in Central and Eastern European countries during both recession and boom periods, as well as in the post-crisis downturn after 2008, in order to achieve stable welfare, confidence in the future for the whole society and the success of long-term investment projects.